2023
DOI: 10.3390/biom13040618
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Fluorescence Imaging of Pancreatic Cancer Using a Fluorescently Labelled Anti-CEA Nanobody Probe: A Preclinical Study

Abstract: Molecular fluorescence-guided surgery using near-infrared light has the potential to improve the rate of complete resection of cancer. Typically, monoclonal antibodies are being used as targeting moieties, however smaller fragments, such as single-domain antibodies (i.e., Nanobodies®) improve tumor specificity and enable tracer injection on the same day as surgery. In this study, the feasibility of a carcinoembryonic antigen-targeting Nanobody (NbCEA5) conjugated to two zwitterionic dyes (ZW800-1 Forte [ZW800F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…VHHs are also suitable for optical imaging, such as near-infrared (NIR) imaging using NIR fluorescent dyes. NIR imaging has been widely developed for molecularly guided precision surgery based on the imaging of specific markers [84]. While complete resection of cancer significantly improves favorable outcomes, distinguishing tumor tissue from benign surrounding tissue is still challenging.…”
Section: Nanobody ® Molecules In Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…VHHs are also suitable for optical imaging, such as near-infrared (NIR) imaging using NIR fluorescent dyes. NIR imaging has been widely developed for molecularly guided precision surgery based on the imaging of specific markers [84]. While complete resection of cancer significantly improves favorable outcomes, distinguishing tumor tissue from benign surrounding tissue is still challenging.…”
Section: Nanobody ® Molecules In Imagingmentioning
confidence: 99%
“…Thus, due to their short circulation time, VHHs are more suitable for non-invasive, shortterm in vivo imaging than fluorochrome-labeled conventional mAbs and offer a promising technology for tumor-specific fluorescence delivery [88]. Studies have shown that ZW800-Fluorescent VHH targeting CEA facilitates visualization of cell lines and patient-derived pancreatic cancers, which better mimic a clinically relevant tumor microenvironment [84,89]. Similarly, a VHH conjugated with IRDye800 targeting carbonic anhydrase IX (CAIX), a specific membrane-bound protein that is upregulated under hypoxic conditions, was able to detect precancerous ductal carcinoma in situ (DCIS) [90].…”
Section: Nanobody ® Molecules In Imagingmentioning
confidence: 99%